Role of the endocannabinoid system in the pathophysiology of endometriosis and therapeutic implications - Harshavardhan Lingegowda; Bailey J. Williams; Katherine G. Spiess; Danielle J. Sisnett; Alan E. Lomax; Madhuri Koti; Chandrakant Tayade (BMC, 2022)
Abstract Endometriosis patients experience debilitating chronic pain, and the first-line treatment is ineffective at managing symptoms. Although surgical removal of the lesions provides temporary relief, more than 50% of the patients experience disease recurrence. Despite being a leading cause of hysterectomy, endometriosis lacks satisfactory treatments and a cure. Another challenge is the poor understanding of disease pathophysiology which adds to the delays in diagnosis and overall compromised quality of life. Endometriosis patients are in dire need of an effective therapeutic strategy that is both economical and effective in managing symptoms, while fertility is unaffected. Endocannabinoids and phytocannabinoids possess anti-inflammatory, anti-nociceptive, and anti-proliferative properties that may prove beneficial for endometriosis management, given that inflammation, vascularization, and pain are hallmark features of endometriosis. Endocannabinoids are a complex network of molecules that play a central role in physiological processes including homeostasis and tissue repair, but endocannabinoids have also been associated in the pathophysiology of several chronic inflammatory diseases including endometriosis and cancers. The lack of satisfactory treatment options combined with the recent legalization of recreational cannabinoids in some parts of the world has led to a rise in self-management strategies including the use of cannabinoids for endometriosis-related pain and other symptoms. In this review, we provide a comprehensive overview of endocannabinoids with a focus on their potential roles in the pathophysiology of endometriosis. We further provide evidence-driven perspectives on the current state of knowledge on endometriosis-associated pain, inflammation, and therapeutic avenues exploiting the endocannabinoid system for its management.